Biomass densification: Effect of cow dung on the physicochemical properties of wheat straw and rice husk based biomass pellets. (March 2019) - Iftikhar, Maira; Asghar, Anam; Ramzan, Naveed; Sajjadi, Baharak; Chen, Wei-yin
Abstract: This study investigates the potential of cow dung, an animal manure, as a binder to enhance the physicochemical properties of the base pellet (a mixture of wheat straw and rice husk). In the first step, preliminary experiments were performed to select the best composition of wheat straw and rice husk for the base pellet. The selection was based on calorific value. Subsequently, the effect of operating parameters such as varying compositions of cow dung (0–100%), molasses concentration (0–100%) and drying time (12–48 h) was investigated. Thus, Central Composite Design using Response Surface Methodology was used to investigate the proximate analysis, calorific value, bulk density and durability of biomass pellets. The experimental results suggested that the addition of cow dung into the base pellet resulted in the increase of volatile matter, ash content, bulk density and durability of the base pellet. As a result, the maximum calorific value of 14.98 MJ/kg, moisture content of 3.37%, volatile matter of 45.49%, ash content of 31.38%, bulk density of 108990 kg/m 3 and durability of 95% were obtained. However, optimization of operating parameters was performed to optimize the ash percentage. With the pellet composition of 8.5% (base pellet composition of 90% wheat straw and 10% rice husk), molasses concentration of 50% and drying time of 12 h, 52% reduction in ash content and 2.3% increase in calorific value were obtained at the cost of 38% reduction in the bulk density and insignificant reduction in durability of the produced pellet. Therefore, the use of waste material like cow dung as a binder can be considered as a sustainable approach to improve the physicochemical properties especially durability of biomass pellets. Thus, it can effectively be used to fulfill the energy and heating requirement of rural areas. Highlights: Utilization of cow dung as binder in pellets composed of wheat straw and rice husk. Production of pellets with maximum calorific value of 19.13 MJ/kg and 98% durability. 52% reduction of ash content by optimizing the % composition of rice husk.